2019
DOI: 10.1021/acs.organomet.9b00019
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum-Mediated Vinylidene Rearrangement of Internal Acylalkynes and Sulfonylalkynes

Abstract: Vinylidene rearrangement of internal acylalkynes and sulfonylalkynes at a d6 molybdenum center is presented. Treatment of [(η7-C7H7)­MoBr­(dppe)] with various acylalkynes R–CC–COR′ in the presence of NaBArF 4 afforded the corresponding vinylidene complexes [(η7-C7H7)­Mo­[CCR­(COR′)]­(dppe)]­[BArF 4], which exist as mixtures of two rotamers, with respect to the MoCα bond at room temperature, as evidenced by NMR studies. This provides the first example of vinylidene rearrangement of internal alkynes at a Mo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Recently our attention has focused on expanding the scope of the vinylidene rearrangenment from the viewpoints of the reaction site and the group migrating. For the former subject, we have demonstrated that d 6 metal centers such as Ir III and Mo 0 are capable of the 1,2-carbon migration . For the latter, we report herein the vinylidene rearrangement of P- and S-substituted internal alkynes at a ruthenium center, in which the heteroatom substituents are the actual migrating groups, as evidenced by 13 C-labeling experiments.…”
Section: Introductionmentioning
confidence: 79%
“…Recently our attention has focused on expanding the scope of the vinylidene rearrangenment from the viewpoints of the reaction site and the group migrating. For the former subject, we have demonstrated that d 6 metal centers such as Ir III and Mo 0 are capable of the 1,2-carbon migration . For the latter, we report herein the vinylidene rearrangement of P- and S-substituted internal alkynes at a ruthenium center, in which the heteroatom substituents are the actual migrating groups, as evidenced by 13 C-labeling experiments.…”
Section: Introductionmentioning
confidence: 79%
“…Transition metal-mediated heavier vinylidene–heavier alkyne rearrangements as the one proposed herein or vice versa have so far not been observed despite significant progress in the synthesis of isolable heavier vinylidenes ,, and heavier alkynes during the last two decades, although the NHC-mediated 1,2-boryl ligand migration from a digermavinylidene to the unsymmetrical mono NHC-stabilized digermyne in the absence of transition metals has been reported by Aldridge and co-workers . In stark contrast, the transition metal-mediated interconversions of all-carbon alkynes and the corresponding vinylidenes are well-established reactions of considerable preparative use. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…In most studies on both catalytic and stoichiometric vinylidene rearrangements, terminal alkynes have been used as active substrates due to the high migration ability of a hydrogen atom . Thus, until recently, internal alkynes have found limited use except for several examples using alkoxycarbonyl-, acyl-, silyl-, stannyl-, sulfanyl-, and halogen-substituted internal alkynes. In this context, even unactivated internal alkynes with alkyl or aryl substituents have been demonstrated to participate in vinylidene rearrangements by us and other researchers, and these findings led to the development of novel catalytic alkyne transformations .…”
Section: Introductionmentioning
confidence: 99%